SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL STUDIES OF NI (II) COMPLEXES WITH SCHIFF BASE CO-LIGAND DERIVED FROM 5,6-DIAMINO-1,10-PHENANTHROLINE AND BENZENE-1,4-DICARBALDEHYDE (FUDMA JOURNAL OF SCIENCES, 2020)
The Schiff base (PDB) was synthesized by refluxing ethanolic solution of 5,6-diamino-1,10-phenanthroline with Benzene-1,4-dicarbaldehyde for 3 hours. Similarly the complexes were synthesized by refluxing equimolar solution of PDB with [Ni(phen)2Cl2] and [Ni(bpy)2Cl2] for 5 hours each and characterized by FTIR, UV-visible, Mass and Elemental Analysis. The absorption band in IR spectrum of PDB at 1593 cm-1 was assigned to C=N stretching frequency which was shifted to 1550 cm-1 and 1549 cm-1 in the spectra of [Ni(phen)2PDB](PF6)2 and [Ni(bpy)2PDB](PF6)2 respectively. The new absorption bands at 721 cm-1 and 754 cm-1 in the spectra of both complexes were due to M-N coordinate bond. The UV- visible absorption band at 390 nm was due to pÂ®p* transitions for azomethine. The low energy band at 450 nm for both complexes is due to MLCT Ni(dp) Â®PDB(p*) transition. The molecular ion peak (M)+ in the mass spectra for PDB and the complexes were observed at 443 m/z, 984.75 m/z and 940.95 m/z respectively. The compounds were evaluated for antimicrobial activities, by well diffusion method against bacteria using agar nutrient as the medium and fungi using potato dextrose agar as medium. The free Schiff base has low activity compared to the complexes with inhibition zone between 4.0 mm to 6.6 mm whereas the complexes ranges from 7.5 mm to 11.2 mm.
Keywords: 5,6-diamino-1,10-phenanthroline, Antimicrobial activities, Nickel (II) complexes and Schiff base.